Unlocking the Value of Indonesia's Underwater Cultural Heritage: A Value Chain Approach to Sustainable Dive Tourism - Kristiadhi, Fanny; Kelana, Himalaya Wana; Nurhayati, Atikah; Dhahiyat, Ahmad Prawira (Journal of Tourism Sustainability, 2025)
Indonesia's vast underwater cultural heritage—comprising shipwrecks, submerged trade routes, and relics of maritime history—represents a unique but underutilised asset within the country's sustainable tourism agenda. This study examines the development of heritage dive tourism in Indonesia, utilising a Value Chain Analysis (VCA) framework to assess how value is created, distributed, and constrained across the sector. Drawing on qualitative data from case studies in the Gaspar Strait, Banda Sea, and North Sulawesi, the research identifies structural gaps in legal protection, site infrastructure, stakeholder coordination, and interpretive engagement. Despite these challenges, emerging community-based initiatives demonstrate the potential for inclusive, conservation-oriented tourism models. Key leverage points were found in the areas of heritage interpretation, community formalisation, and digital promotion. The results underscore the need for an integrated governance model that incorporates local participation at every level of the tourism value chain and aligns with the principles of the Blue Economy. This study presents a strategic framework for promoting sustainable, culturally rich marine tourism in emerging maritime economies by utilizing the VCA approach to examine underwater cultural heritage.